The Influence of Globalization on International Law Between Two Countries - I Putu Nuriyanto; Cokorde Istri Dian Laksmi Dewi; Kadek Ary Purnama Dewi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract Globalization has brought significant changes in international relations, particularly through increased interaction in the fields of economics, politics, society, and law. One of the most evident impacts of globalization is the growing influence of international law on national legal systems. Indonesia, as part of the global community, has begun adopting various international legal principles, especially in the areas of trade and communication, making its national law more open and transnational in nature. This development also demands that law be more responsive to social dynamics and public policy. Law is no longer static, but must be able to interact with societal interests and the international community. However, globalization also presents challenges, particularly concerning differences in legal systems between countries, such as common law and civil law. To address this, legal harmonization is necessary, aligning principles and procedures through bilateral negotiations, international conventions, or the adoption of model laws from institutions such as UNCITRAL. Fields such as trade, arbitration, and human rights demonstrate the importance of legal harmonization, provided it still respects the legal sovereignty of each country. Keywords: Globalization, International Law, Two Countries